Using the COM-B model to identify barriers to and facilitators of evidence-based nurse urine-culture practices - Sonali D. Advani; Ali Winters; Nicholas A. Turner; Becky A. Smith; Jessica Seidelman; Kenneth Schmader; Deverick J. Anderson; Staci S. Reynolds (Cambridge University Press, 2023)
Our surveys of nurses modeled after the Capability, Opportunity, and Motivation Model of Behavior (COM-B model) revealed that opportunity and motivation factors heavily influence urine-culture practices (behavior), in addition to knowledge (capability). Understanding these barriers is a critical step towards implementing targeted interventions to improving urine-culture practices.